Evaluation of Proinflammation Interleukin-18 (IL-18) in Thyroid Disorders Patients in Najaf Province - Naser, Naser Adris; Mahmood , Thikra Abdullah (Medical Science Journal for Advance Research, 2024)
Background: Iodine shortage or autoimmune illnesses can lead to thyroid problems. Graves’ disease and Hashimoto’s disease are examples of autoimmune thyroid diseases (AITDs) that develop when the immune system becomes unbalanced and attacks the thyroid gland. A subset of autoimmune disorders, AITDs target only one thyroid gland. Aim the study: Finding out how interleukins IL-18 affect thyroid disease patients is the primary goal of the study. Methods: Participants ranged in age from 18 to 70 and visited Sadr Medical City’s Diabetes and Endocrinology department, the specialty of Al-Zahraa Laboratory, and other laboratories in Najaf Governorate between July and October 2023. Out of a total of 400 samples, 140 underwent immunodiagnostics, and the remaining 70 served as control groups. Results Test subjects were compared to a control group based on their T3, T4, and TSH concentrations, which were used to diagnose hypothyroidism and hyperthyroidism, respectively. Compared to both the control group and the other patients, those with hypothyroidism had substantially lower T3, T4, and TSH intensities, but a significantly higher TSH majority of the subjects tested had hypothyroidism. Following this, in addition to the doctor’s clinical diagnosis, patients underwent specialized testing to identify the existence of antibodies linked to this illness (AITD), namely ATPO and ATG. Secondly, compared to normal controls, people with Graves’ disease and Hashimoto’s disease had much higher ATG levels, and patients with both Graves’ disease and HD had much higher ATPO concentrations. This study showed a higher incidence of AITD in females, as it was in Graves (84.8%) and Hashimoto’s (77.1%), and the age group 30–50 years was more frequent in Graves (51.5%) and Hashimoto’s (62.9%). the hypothyroid group consisted of 29 patients (78.6% of the total) and the non-smoking group of 27 patients (81.8%), with 8 hypothyroid patients (21.6%) and 6 non-smoking patients (19.4% of the total) serving as controls. Among the research groups, smoking status significantly altered the frequency distribution (p = 0.0.03). There was a significant mental state (p-value < 0.05 was 0.00001). When it comes to Hashimoto’s and Graves’, TSH, T3, T4, antTPO, and antTG bind. Researchers have shown that thyroid illnesses (namely Hashimoto’s disease and Graves’ disease) are associated with elevated serum IL-18 levels (9.665 and 9.636, respectively). Compared to the healthy group (mean = 9.192), there is no significant difference in the p-value ⋤ 0.05. Similarly, there is no significant difference between C1 and C2 (p-value < 0.05). Conclusion of this study to the crucial role of interleukin-18 in individuals suffering from thyroid diseases. Thyroid disorders and mental status are distinct from pro-inflammatory cytokines, which have a positive correlation with psychopathology through multiple mechanisms affecting neurodevelopment, transmission, and synaptic plasticity; anti-TOP and anti-TG medications have a strong impact on IL18 and other pro-inflammatory cytokines. The "double effect" that women have makes thyroid diseases more common in women than in men. In terms of smoking, there was a notable difference in the frequency distributions across the study groups.